Perancangan Kerangka Crowdsourcing Berbasis Wisdom Of Crowds Untuk Kamus Naskah Lontar (Takepan) Sasak Online - Muhammad Saiful; L M Samsu; Imam Fathurrahman (Fakultas Teknik Universitas Hamzanwadi, 2020)
The online Lontar (Takepan) Sasak manuscripts currently available are not sufficient to be a reference for those who want to learn Sangsekerta because of the limited contribution and stagnation of their contributions. On the other hand, active speakers of Lontar (Takepan) Sasak manuscripts exposed to the internet are available in sufficient quantities. The wisdom of crowds-based crowdsourcing mechanism is expected to be a solution to the problem. This paper presents a draft framework of the Sasak Lontar (Takepan) online crowdsourcing dictionary system. The design of this framework is expected to be the basis for the development of the new Sasak Lontar (Takepan) online dictionary.DOI : 10.29408/jit.v3i2.2300